2023
DOI: 10.3389/fphar.2022.1098634
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stromal cell-derived small extracellular vesicles: A novel therapeutic agent in ischemic heart diseases

Abstract: Myocardial injury is a major pathological factor that causes death in patients with heart diseases. In recent years, mesenchymal stromal cells (MSCs) have been generally used in treating many diseases in animal models and clinical trials. mesenchymal stromal cells have the ability to differentiate into osteocytes, adipocytes and chondrocytes. Thus, these cells are considered suitable for cardiac injury repair. However, mechanistic studies have shown that the secretomes of mesenchymal stromal cells, mainly smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…MSCs can differentiate into bone cells, fat cells, and chondrocytes, which are considered suitable for heart damage repair. Many studies have shown that the secretions of MSCs, mainly EVs, have better therapeutic effects than the MSCs themselves 199 . EVs allow for easier quality control and better biosecurity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs can differentiate into bone cells, fat cells, and chondrocytes, which are considered suitable for heart damage repair. Many studies have shown that the secretions of MSCs, mainly EVs, have better therapeutic effects than the MSCs themselves 199 . EVs allow for easier quality control and better biosecurity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the secretions of MSCs, mainly EVs, have better therapeutic effects than the MSCs themselves. 199 EVs allow for easier quality control and better biosecurity. Therefore, MSC‐derived EVs are becoming a new therapeutic approach for treating CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was observed that this combination resulted in a decrease in the development of microcirculation thrombi within the affected region, an improvement in endothelial barrier function, and an increase in microvascular density in the injured area. 4 However, in specific circumstances, EVs can play a role in the mechanism of cardiovascular diseases (CVDs). 5 Serum EVs, for instance, play a part in the progression of pulmonary arterial hypertension and vascular calcification.…”
Section: Dear Editormentioning
confidence: 99%
“…In recent years, many studies have shown that sEVs carry bioactive cargoes, including lipids, proteins, and nucleic acids, which mediate cell-cell communication and regulate biological functions in recipient cells. 10,11 In diabetic condition, serum sEVs were shown to carry sonic hedgehog, a protein that modulates immunity, or arginase1 to induce endothelial dysfunction. 12 In addition, numbers of noncoding RNA are shown to carry by sEVs and are associated with incidence of diabetic complications.…”
Section: Introductionmentioning
confidence: 99%
“…However, some EVs are produced by direct budding from the plasma membrane, which also has size of 50–200 nm, and they cannot be distinguished by current isolation methods, 9 so the term of sEVs represents vesicles (50–200 nm) that are generated by both pathways. In recent years, many studies have shown that sEVs carry bioactive cargoes, including lipids, proteins, and nucleic acids, which mediate cell–cell communication and regulate biological functions in recipient cells 10,11 . In diabetic condition, serum sEVs were shown to carry sonic hedgehog, a protein that modulates immunity, or arginase1 to induce endothelial dysfunction 12 .…”
Section: Introductionmentioning
confidence: 99%